Polimorfisme Protein Darah Domba di Kabupaten Batanghari - Erina, Silvia; Ediyanto, Helmi (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2012)
In  Pemayung and Muara Bulian Subdistrict, Batanghari District, the population of sheep is relatively high. However, information on  genetic characteristics of the sheep has not been well-identified yet . Therefore, in order to reach one of the objectives of veterinary development, conservating local breeds, it is necessary to know blood protein polymorphism of the sheep. One way to identify genetic characteristic of the sheep is by analizing blood protein  electrophoretically.The research is aimed at analizing genetic characteristics of sheep in Batanghari District, including characteristics of blood protein by electrophoresis to know blood protein polymorphism patterns. Blood samples were taken from 20 sheep, 10 sheep from Pemayung Subdistrict and 10 sheep from Muara Bulian Subdistrict. Analysis was conducted at Livestock Molecular  Genetic Laboratory Veterinary Faculty Bogor Agriculture Institute. Allelic Frequency was directly calculated with Hardy-weinberg proportion and genetic distance is was calculated with method of Nei . The result of electrophoretic analysis  has found 5 kinds of proteins ; Albumin, Postalbumin, Transferin, Posttransferin-1 and Posttransferin-2. Albumin and Postalbumin are controlled by 2 alleles ; Allele A=0,6 and allele B=0,4, Transferin is controlled by 4 alleles ; allele A = 0,025, allele B=0,50, allele C=0,45, and allele D=0,025. Posttransferin-1 and posttransferin-2 are controlled by an allele; allele A=1,00. In conclusion, there are 5 kinds of blood protein, they are Albumin, Postalbumin, Transferin, Posttransferin-1 and Posttransferin-2.Polymorphism is detected in 3 loci; Albumin, Postalbumin and Transferin with Heterozigocity Average 0,29 in Pemayung Subdistrict and 0,287 in Muara Bulian Subdistrict. Albumin and Postalbumin loci can be considered as main genetic characteristics.